ESG POLICIES AS A TOOL FOR MARKETING MANAGEMENT OF THE ENTERPRISE COMPETITIVENESS IN THE FOOD MARKET - TARANENKO, Iryna; KOKARIEV, Illia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the role of ESG (Environmental, Social, Governance) policies as a tool for marketing management of enterprise competitiveness in the context of growing consumer awareness of sustainable development. The study analyses consumer preferences related to purchasing decisions that incorporate sustainability considerations, based on data from international surveys. The findings reveal that consumers pay the greatest attention to environmental friendliness and sustainable practices when purchasing food products, non-alcoholic beverages, and confectionery goods. It is established that a significant proportion of consumers take into account environmental and social factors when making decisions about buying food, beverages, and confectionery, prioritizing such tangible factors as eco-friendly packaging, natural ingredients, food safety, and support for local producers and farmers. The research proves that ESG approaches serve as an effective driver for strengthening the competitive position of enterprises in the food market by creating long-term competitive advantages through building consumer trust and loyalty, enhancing positive brand perception, increasing reputational capital, and stimulating recommendation behaviour (word of mouth). The analysis demonstrates that companies which consistently implement ESG policies attract new customers and retain existing ones due to a stronger alignment with consumer values, as customers increasingly prefer brands that reflect their ethical, environmental, and social expectations. Thus, the paper substantiates that the consistent integration of ESG policies is an effective marketing management tool that ensures increased sales volumes and market share by attracting and retaining customers through value-based interaction within the context of sustainable development. Enterprises that apply ESG-driven marketing policies not only gain competitive benefits in terms of customer loyalty and brand equity but also contribute to broader social and environmental goals, enhancing their long-term sustainable competitiveness.